Think-Aloud Protocols in Second Language Writing A Mixed-Methods Study of Their Reactivity and Veridicality - Yang, Chengsong; Zhang, Lawrence Jun. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book addresses the validity of think-aloud protocols (TAPs) in L2 writing research through a mixed methods study and proposes effective approaches for their valid implementation. The book uncovers the reactive effects that TAPs have on L2 writing performance and processes, and examines how individual factors moderate this reactivity. It further presents and categorizes participants' perceptions regarding reactivity and veridicality. To enhance veridicality, the book identifies incomplete TAPs using retrospective verbal reports as a reference point. Recommendations for utilizing TAPs include considering participants' individual differences, recent experiences, and emotions. This book will be valuable to educators teaching methodology in second or foreign language education, applied linguistics, or writing research, and to L2 researchers or graduate students with a broad interest in research methods, process-based research, or writing studies, or planning to incorporate TAPs into their research.
Foreword by Rod Ellis -- Introduction -- Literature Review -- Methodology -- Reactivity: Results from Quantitative Analyses of Performance -- Reactivity: Results from Qualitative Analyses of Reflections -- Veridicality: Results from Qualitative Analyses of Reflections -- Veridicality: Results from Comparison of Reports -- Discussion -- Conclusions, Limitations, and Implications for Using TAPs.
Keywords: Language and languages -- Study and teaching; Applied linguistics; Language Education; Language Teaching and Learning; Applied Linguistics